ANALISIS KINERJA PT. X DENGAN MENGGUNAKAN BALANCED SCORECARD UNTUK MENDUKUNG SISTEM PENGAMBILAN KEPUTUSAN - Budi Harsono; Meiliyah Ariani (LPPM UNIVERSITAS BINA INSAN, 2017)
PT. X is a company that produces straws and sticks for lollipops. The raw materials used for production are plastic ores. Demand for plastic ore is currently high and volatile. This makes it difficult for the company to determine how much raw materials it needs to get suppliers that match the company's criteria. Therefore, supplier performance appraisal is required. The result of supplier performance calculation using Balanced Scorecard shows that supplier 4 is the best supplier owned by PT. X. By applying supplier performance appraisal, it will help PT. X in decision making.